Efficacy of Corticosteroids Alone in the Eradication of Factor VIII Inhibitor in an Old Female with Idiopathic Acquired Haemophilia A: Description of a Case. (29th August 2012) - Girelli, Francesco; Biasoli, Chiara; Bassi, Bruna; Bagioni, Franco; Bondi, Gabriele; Camporesi, Claudio; Gardelli, Lucia; Mazzeo, Vincenzo; Nizzoli, Maurizio
Abstract : Acquired haemophilia A (AHA) is a rare and serious disorder mainly affecting elderly patients. It is caused by the production of autoantibodies directed against coagulation factors; patients present with spontaneous bleeding, potentially fatal, in the absence of familial or personal history. Autoimmune disorders, infections, solid and hematologic tumors, and drugs are predisposing factors, but up to 50 percent of cases remain unexplained. The diagnosis of AHA is confirmed by specific laboratory tests; and the therapy is a clinical challenge, due to the fact that older patients are often affected by comorbidities. By passing agents may be used when persistent bleeding or haemodynamic instability is observed; corticosteroids, alone or with immunosuppressive therapy, are necessary to inhibit the production of the autoantibodies. We describe a case in which steroids in monotherapy successfully, safely, and persistently inhibited the production of anti-Factor VIII antibodies, in an old patient admitted after rheumatologic consult.